Embryonic and larval development of the mojarra paleta Vieja melanura (Günther, 1862) from the mexican southeast - Hernández-Hernández, Francisco Antonio; Hernández-Gómez, Raúl Enrique; Valenzuela-Cordova, Ignacio; Perera-García, Martha Alicia; Cuenca-Soria, Carlos Alberto (Ecosistemas y Recursos Agropecuarios, 2020)
Previous studies of Vieja melanura consider population aspects, without addressing reproductive references, which are useful for fisheries and aquaculture management plans. The objective of this study was to determine the initial ontogeny of the species up to the juvenile stage under controlled conditions. All descriptions were based on morphometric and myristic data; following standard methods. The fertilized eggs measured an average of 2.38 mm in diameter, the newly hatched larvae of 3.80 mm of TL, which hatched after 14 h. The final flexion stage in the larva occurred 6 days after hatch, and the yolk sac was 95% reabsorbed. The larvae in the post-flexion stage measured an average of 8.45 mm TL. Pre-juvenile 15.70 mm TL and juvenile was 23.65 mm at 35 dph.